2019
DOI: 10.3390/en12142775
|View full text |Cite
|
Sign up to set email alerts
|

An Enhanced Flow-Thermo-Structural Modeling and Validation for the Integrated Analysis of a Film Cooling Nozzle Guide Vane

Abstract: The target of this paper is to develop an enhanced flow-thermo-structural (FTS) model with high computational accuracy, to perform the integrated analysis of film cooling nozzle guide vane (NGV). An efficient turbulence model and weak spring approach are utilized in the enhanced FTS model. In respect of the power balance principle of aeroengine rotor shaft and temperature test of a typical combustor, the mean temperature inlet and five normalization temperature curves were confirmed, respectively. The temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Numerical simulations are used to find the cooling effectiveness of turbine blades and NGVs. Results of the simulations are validated against experimental results, such as those from temperature-sensitive paints [16]. Finite element modelling (FEM) can be used to predict the thermal load on a blade and analyse the effectiveness of blade cooling methods.…”
Section: Numerical Methods For Temperature Estimationmentioning
confidence: 99%
“…Numerical simulations are used to find the cooling effectiveness of turbine blades and NGVs. Results of the simulations are validated against experimental results, such as those from temperature-sensitive paints [16]. Finite element modelling (FEM) can be used to predict the thermal load on a blade and analyse the effectiveness of blade cooling methods.…”
Section: Numerical Methods For Temperature Estimationmentioning
confidence: 99%
“…Sci. 2019, 9,4357 6 of 21 were defined as the subdomain of the master model in the positions. To prevent a large volume ratio of grid elements in the master model, the subdomain was slightly larger than the slave model.…”
Section: Physical Model and Meshing Methodsmentioning
confidence: 99%
“…Based on the BC test results, the life of the TBC was predicted by Song [8], according to degradation and thermal fatigue. Many experiments indicated that the failure of the TBC systems under thermomechanical loading was complicated due to the influences of many factors such as thermal mismatch, oxidation, interface roughness, creep, sintering, and so forth [9][10][11]. Among the failure factors, the effect of TGO growth is particularly prominent, because volume expansion and compressive stress increase are correlative with the growth of TGO.…”
Section: Introductionmentioning
confidence: 99%
“…In the online monitoring of aeroengine, sensors are mainly installed on the outer surface of casings to monitor the health status of rolling bearing, so that too long signal propagation path induces vibration signals attenuation, low signal to noise ratio (SNR) of fault signals, and difficult extraction of fault features [1]. erefore, it is urgent to study the weak fault diagnosis of intershaft bearings [2][3][4].…”
Section: Introductionmentioning
confidence: 99%